The Category of Performance in Hannah Arendt - Goyenechea, Elisa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The paper inquires the category of performance in Hannah Arendt. Her concept of the political eludes the tradition-inherited approach and subtracts the praxis from instrumental reason. Arendt revisits the political experiences of ancient Greek cities, where tragedy and assembly, theater and agora, provide the propitious space for action. She avoids the instrumental approach of homo faber, conceptualizes action as performance and shows its connaturality with the performing arts, to the detriment of the productive ones. In “What is Freedom?” Arendt understands political freedom as a “worldly fact”, and assesses the Machiavellian virtù as public excellence: as performance on stage.